Synthesis, optical and electrochemical properties of isomeric dibenzophenanthroline derivatives - Ghosh, Animesh (2021)
Acid catalysed Friedländer cyclization of 2-aminobenzophenones with 1,2-, 1,3-, and 1,4-cyclohexadiones, followed by aromatization, has been used to prepare dibenzophenanthrolines (DBPs) containing 1,10-, 1,7- and 4,7-phenanthroline units, whose optoelectronic properties have been compared. The LUMO energies for all isomers were similar but the 4,7-isomers possessed significantly higher HOMOs than the other isomers, resulting in them having smaller HOMO-LUMO energy gaps. Compared with 1,10-DBP isomers, the emission of 1,7-DBPs is strongly quenched due to efficient charge transfer. The 4,7-DBP isomers show strongly enhanced photoluminescence due to excimer formation but appear to be less photostable due to their higher HOMO levels. Bis(phenylethynyl)-substituted derivatives demonstrated improved solubility and stronger luminescence properties than their unsubstituted analogues.